Synthesis of fluorinated acid-functionalized, electron-rich nickel porphyrins - Brockmann, Mike; Lobbel, Jonas; Unterriker, Lara; Herges, Rainer (Beilstein Journal of Organic Chemistry, 2024)
In this study, novel fluorinated carboxylic acid esters of the generic structure TfO–CH2–(CF2)n–COOCH3 (n = 2,4,6, Tf = triflate) were synthesized. The triflates were reacted with 2-hydroxy-3,4,5-trimethoxybenzaldehyde via Williamson ether syntheses. The resulting electron-rich compounds were used as aldehydes in the Rothemund reaction with pyrrole to form ester-substituted porphyrins. After metalation with Ni(acac)2 and hydrolysis electron-rich porphyrins were obtained, that are equipped with covalently attached long chain acid substituents. The target compounds have potential applications in catalysis, sensing, and materials science. The fluorinated aliphatic carboxylic acids (TfO–CH2–(CF2)n–COOCH3) with triflate as leaving group in terminal position are easily accessible and versatile building blocks for attaching long chain acids (pKa 0–1) to substrates in Williamson ether-type reactions.
Keywords: acid-functionalized porphyrin; electron-rich porphyrin; nickel porphyrin; perfluorinated aliphatic carboxylic acids; porphyrin synthesis